2019
DOI: 10.1364/boe.10.000610
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantification study of human cardiomyocyte synchronization using holographic imaging

Abstract: This paper investigates the rhythm strip and parameters of synchronization of human induced pluripotent stem cell (iPS) derived cardiomyocytes. The synchronization is evaluated from quantitative phase images of beating cardiomyocytes which are obtained using the time-lapse digital holographic imaging method. By quantitatively monitoring the dry mass redistribution, digital holography provides the physical contraction-relaxation signal caused by autonomous cardiac action potential. In order to analyze the synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…For example, Moon et al reported the observation of rhythm strip and parameters of synchronization of human-induced pluripotent stem cell (iPS). [23,24] Mugunano et al evaluated cadmium-induced cell apoptosis. [25] Ugele et al quantitatively compared differentiation of leukocytes (DIFF) with eight leukocyte subtypes.…”
Section: Methods Detailsmentioning
confidence: 99%
“…For example, Moon et al reported the observation of rhythm strip and parameters of synchronization of human-induced pluripotent stem cell (iPS). [23,24] Mugunano et al evaluated cadmium-induced cell apoptosis. [25] Ugele et al quantitatively compared differentiation of leukocytes (DIFF) with eight leukocyte subtypes.…”
Section: Methods Detailsmentioning
confidence: 99%
“…2 ) [ 63 , 64 ]. Thereby, contraction and relaxation velocity as well as deformation distance can be determined, serving as surrogate parameters for force generation [ 62 , 63 , 65 ]. Due to its accessibility and unpretentious technique, this approach is widely used and scalable for approaches in multiwell plate formats in order to perform high-content screening assays using contractility as a readout.…”
Section: Analysis Of Hipsc-cm Modelsmentioning
confidence: 99%
“…The off-axis configuration (see Fig. 1) was shown to be very useful in different studies of biological samples [15][16][17][18][19][20][21][22] and dynamic topography [23,24]. Off-axis configuration for studying biological samples is called digital holographic microscopy (DHM) [17].…”
Section: Introductionmentioning
confidence: 99%